The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1038/s41419-021-03814-5
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic regulation of intestinal peptide transporter PEPT1 as a potential strategy for colorectal cancer sensitization

Abstract: Human intestinal peptide transporter PEPT1 is commonly repressed in human colorectal cancer (CRC), yet its relationship with sensitivity to the common CRC treatment ubenimex has not previously been elucidated. In this study, we confirmed PEPT1 suppression in CRC using real-time quantitative polymerase chain reaction and western blotting and then investigated the underlying epigenetic pathways involved using bisulfite sequencing, chromatin immunoprecipitation, siRNA knockdown, and reporter gene assays. We found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 64 publications
1
8
0
Order By: Relevance
“…A Chinese cohort GWAS comprising 3,406 cases of bladder cancer and 4,645 controls identified a new susceptibility locus for BCa in the intron of CWC27 (rs2042329) [ 11 ]. SCL15A1, also called PEPT1, was reported to be a highly expressed drug target protein in many different human cancers, including colorectal cancer [ 12 ], gastric cancer [ 13 ], hepatocarcinoma cells [ 14 ], and prostate cancer [ 15 ]. SCL15A1 is one of the important molecules during cancer development.…”
Section: Introductionmentioning
confidence: 99%
“…A Chinese cohort GWAS comprising 3,406 cases of bladder cancer and 4,645 controls identified a new susceptibility locus for BCa in the intron of CWC27 (rs2042329) [ 11 ]. SCL15A1, also called PEPT1, was reported to be a highly expressed drug target protein in many different human cancers, including colorectal cancer [ 12 ], gastric cancer [ 13 ], hepatocarcinoma cells [ 14 ], and prostate cancer [ 15 ]. SCL15A1 is one of the important molecules during cancer development.…”
Section: Introductionmentioning
confidence: 99%
“…SLC4A4 and SLC9A3 can transport H + and HCO 3 – , respectively, thus affecting tumor cell PH regulation. SLC15A1 has a significant effect on intestinal peptide transport affects intestinal diseases. , SLC38A3 is known for its involvement in amino acid transport and is extensively documented in neurological disorders. Previous studies have explored the role of SLC38A3 in glutamine metabolism and its effect on tumor progression. Our study identified SLC38A3 as a novel prognostic marker gene in CRC, and the knockdown of SLC38A3 in HCT cells inhibited CRC cell proliferation and migration.…”
Section: Discussionmentioning
confidence: 99%
“…There is little understanding of epigenetic regulation of PEPTs until very recently. Wang et al reported a suppressed expression of SLC15A1 (PEPT1) in colon cancer due to DNA methylation and histone deacetylation (Wang et al, 2021a). DNA methyltransferase 1 was characterized as the primary determinant of the hypermethylation of SLC15A1 proximal promoter.…”
Section: Transcriptional Regulation Of Peptsmentioning
confidence: 99%